2021
DOI: 10.3389/fmed.2020.600049
|View full text |Cite
|
Sign up to set email alerts
|

Knee Cartilage Thickness Differs Alongside Ages: A 3-T Magnetic Resonance Research Upon 2,481 Subjects via Deep Learning

Abstract: Background: It was difficult to distinguish the cartilage thinning of an entire knee joint and to track the evolution of cartilage morphology alongside ages in the general population, which was of great significance for studying osteoarthritis until big imaging data and artificial intelligence are fused. The purposes of our study are (1) to explore the cartilage thickness in anatomical regions of the knee joint among a large collection of healthy knees, and (2) to investigate the relationship between the thinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…However, both studies enrolled arthritic subjects where pathological cartilage wear or defects were expected. A similar trend was reported by Si et al, who reported 1.75 ± 0.12 mm for the medial distal femoral cartilage and 1.77 ± 0.13 mm for the lateral, and 1.59 ± 0.16 mm for the medial posterior femoral cartilage and 1.61 ± 0.22 mm for the lateral ( 18 ). The thickness difference could be explained by the subjects we recruited, who were involved in high-intensity physical activities ( 19 ).…”
Section: Discussionsupporting
confidence: 89%
“…However, both studies enrolled arthritic subjects where pathological cartilage wear or defects were expected. A similar trend was reported by Si et al, who reported 1.75 ± 0.12 mm for the medial distal femoral cartilage and 1.77 ± 0.13 mm for the lateral, and 1.59 ± 0.16 mm for the medial posterior femoral cartilage and 1.61 ± 0.22 mm for the lateral ( 18 ). The thickness difference could be explained by the subjects we recruited, who were involved in high-intensity physical activities ( 19 ).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to Norman et al [ 46 ], Si et al [ 47 ] decided to use 2D U-Net to segment the bones and articular cartilages of the knee from MR images which are femur, tibia, patellar, and each of their corresponding cartilages. The cartilages are segmented to obtain the cartilage thickness in 14 anatomical regions.…”
Section: Application Of 2d Deep Learning In Knee Osteoarthritis Assessmentmentioning
confidence: 99%
“…Wirth et al [ 31 ] also used 2D U-Net for segmenting femorotibial cartilages to test the cartilage morphometry longitudinal test-retest reproducibility and had demonstrated high DSC for both coronal FLASH and sagittal DESS images. For both studies by Si et al [ 47 ] and Wirth et al [ 31 ], only subjects without OA were included.…”
Section: Application Of 2d Deep Learning In Knee Osteoarthritis Assessmentmentioning
confidence: 99%
“…7 The problem can be addressed by fully automated approaches, which typically require segmenting cartilage in the MR images, defining joint regions and subregions, and calculating mean cartilage thickness per region and subregion. Different approaches for cartilage thickness measurements have been developed previously, for example, (1) finding the minimum distance between opposite cartilage surfaces, [8][9][10][11][12] (2) measuring the lengths of surface normals between 3D meshes that approximate the cartilage surfaces, 6,8,11,13 (3) combining surface normals with offset maps, 14 (4) analyzing shape models fitted to the cartilage volume, 15 or (5) computing curved potential field lines between the cartilage surfaces. 11 Commercially available techniques also rely on the calculation of surface normals between meshes, 6 which may thus be considered the most established method to date.…”
Section: Introductionmentioning
confidence: 99%